Simplificación administrativa municipal ¿imposición o iniciativa propia? - Castillo Mendives, Ángela (2006)
In 2006, thanks to an international cooperation project, an administrative simplifi cation process was implemented in a Peruvian province municipality to evaluate and modify the stages for the issuance of operation permits. As this initiative was organized by the cooperating institution, access to information was not complete and this resulted in overlapped efforts, additional time investment, changes in the budget and, above all, some inaccuracies in the expected results, which were noticed at the end of the consultation process by the municipality’s own staff. This case will demonstrate the importance of taking into account the points of view of an organization’s members during the decision-making process, as this is the key to success in any change initiative.